Long Range Planning and Sustainability of Projects in Greater Kabale Uganda - Agaba , Moses; Turyasingura, John Bosco (International Journal of Applied Management and Business, 2025)
This study was set to examine the effect of long-range planning and sustainability of projects in greater Kabale district a case of Projects Implemented by The International Fertilizer Development Center (IFDC).The study followed a cross sectional survey design. Data from 163 respondents was collected and analyzed quantitatively complemented with qualitative analysis. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. A linear regression model was used to fit the data. Research findings from the regression model show that long range planning affects sustainability of projects among the projects implemented by IFDC in greater Kabale District with (R=762), The results and discussion above make it abundantly evident that IFDC in greater Kabale District long range planning restrictions are a strong predictor of sustainability of projects in greater Kabale District. This highlights how crucial it is for IFDC to always involve projects stakeholders in long range planning if projects are to be sustainable. In order to ensure sustainability of projects implemented by IFDC in greater Kabale District the study recommended that, all projects beneficiaries should get involved in all activities of the organization from conception stage to project termination. This is when IFDC projects will be sustainable after donor exit.